2010
DOI: 10.1021/ml100268k
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent and Short−Acting Oral Calcilytic with a Pulsatile Secretion of Parathyroid Hormone

Abstract: Short-acting oral calcilytics, calcium-sensing receptor (CaSR) antagonists, have been considered as alternatives for parathyroid hormone (PTH), an injectable bone anabolic drug used in the treatment of osteoporosis. Previously, we identified aminopropandiol 1, which transiently stimulated endogenous PTH secretion in rats. However, the inhibition of cytochrome P450 (CYP) 2D6 and the low bioavailability of 1 remain to be solved. Attempts to change the physicochemical properties of the highly lipophilic amine 1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“…Replacement of the phenyl ether of NPS 2143 by a 2-methylbenzyloxy group and the addition of a cyclopropyl substituent at the benzylic position afforded compound 1 (FiguRe 2), which was not only equipotent to NPS 2143 in vitro, but also induced a rapid and transient increase of endogenous plasma PTH at a dose of 10 mg/ kg in rats. Unfortunately, the bioavailability of 1 was low (13%) and the compound showed strong inhibition for CYP 2D6 [43], as was seen for NPS 2143. It was shown that a COOH group could be accommodated without loss of CaSR antagonist activity in the form of an ortho propionic acid substituent (2; FiguRe 2).…”
Section: Amino Alcoholsmentioning
confidence: 94%
See 1 more Smart Citation
“…Replacement of the phenyl ether of NPS 2143 by a 2-methylbenzyloxy group and the addition of a cyclopropyl substituent at the benzylic position afforded compound 1 (FiguRe 2), which was not only equipotent to NPS 2143 in vitro, but also induced a rapid and transient increase of endogenous plasma PTH at a dose of 10 mg/ kg in rats. Unfortunately, the bioavailability of 1 was low (13%) and the compound showed strong inhibition for CYP 2D6 [43], as was seen for NPS 2143. It was shown that a COOH group could be accommodated without loss of CaSR antagonist activity in the form of an ortho propionic acid substituent (2; FiguRe 2).…”
Section: Amino Alcoholsmentioning
confidence: 94%
“…Incorporation of the short linker chain between the phenyl ring and the carboxylic acid group into a phenyl ring and replacement of the naphthyl group by the 4-chloro-3-fluorophenyl residue (crucial for good bioavailability) finally led to JTT-305 (FiguRe 2). The methyl group ortho to the COOH unit was found to improve in vivo potency, which was attributed to slower metabolic degradation caused by steric hindrance [43].…”
Section: Amino Alcoholsmentioning
confidence: 99%
“…Several further modifications of NPS 2143 structure led to the development of another calcilytic compound, JTT-305 by Japan Tobacco, Inc. [96], subsequently bought by Merck (and therefore termed MK-5442). JTT-305/MK-5442 was demonstrated to stimulate pulsatile PTH secretion and bone formation in ovariectomized rats [97].…”
Section: Calcilytics: Effects On Bonementioning
confidence: 99%
“…Japan Tobacco Inc. developed JTT‐305/MK‐5442, an orally bioavailable, high‐affinity calcium‐sensing receptor (CaSR) allosteric antagonist that is being investigated for the treatment of osteoporosis . JTT‐305/MK‐5442 binds reversibly to CaSR and does not share binding sites with Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…J apan Tobacco Inc. developed JTT-305/MK-5442, an orally bioavailable, high-affinity calcium-sensing receptor (CaSR) allosteric antagonist that is being investigated for the treatment of osteoporosis. (1)(2)(3)(4)(5) JTT-305/MK-5442 binds reversibly to CaSR and does not share binding sites with Ca 2þ . The binding ability of 3 H-labeled JTT-305/MK-5442 was studied using a cell membrane fraction of African green monkey kidney-derived cells (COS-7) expressing the human CaSR.…”
Section: Introductionmentioning
confidence: 99%